Pelabelan Total Titik Ajaib Pada Graf Tangga - Riandy Fauzi Manik; Marlina Setia Sinaga (Lembaga Pengembangan Kinerja Dosen, 2023)
The labeling of a graph is a mapping that pairs the elements in the graph into positive integers. In this thesis, it discusses how the magic total point labeling algorithm on the ladder graph and the ladder graph and how the magic total point labeling on the ladder graph and the adder graph uses the magic square matrix modification using the durer method. Where the elements of the result of this magic square matrix modification will be used as point labels on the ladder graph and the ladder graph.